Impact of Dual Careers on Average Family Size: Comparison of 11 Countries - Lynn Prince Cooke (Luxembourg Income Study (LIS), 2001)
While more and more married women participate in paid work, men have not equalized the division of labor by appreciably increasing the time they devote to unpaid domestic tasks. The state can assist in managing this double time burden on women by enabling families to externalize a portion of it via social provisions supporting maternal employment. This paper presents a formal model of family time and resource distribution, women's constraints therein, and the impact the market or social provisions can have in alleviating the strains between production and reproduction. The extent to which the externalization of the burden of care maintains both female labor force participation and family size is then analyzed for 11 countries in the mid-1980s and mid-1990s using data from the Luxembourg Income Study.
Keywords: 330; Haushaltseinkommen; Erwerbsverlauf; Kinder; Familie; OECD-Staaten; Ehe